Principle of objectivity and classical physics. (1979) - Dutta, M.; Basu, U.
Abstract : In literature, it is generally asserted that the principle of objectivity is valid for constitutive equations but not valid for general field equations. In this paper, the principle of objectivity is formulated clearly to emphasize the correct significance, and necessity of the principle and to discuss its validity in physical theories. A discussion is made to show how successfully the principle of objectivity is also applicable to non-relativistic classical physics.